2007
DOI: 10.1371/journal.pgen.0030200
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Drosophila Greatwall/Scant Reveal Its Roles in Mitosis and Meiosis and Interdependence with Polo Kinase

Abstract: Polo is a conserved kinase that coordinates many events of mitosis and meiosis, but how it is regulated remains unclear. Drosophila females having only one wild-type allele of the polo kinase gene and the dominant Scant mutation produce embryos in which one of the centrosomes detaches from the nuclear envelope in late prophase. We show that Scant creates a hyperactive form of Greatwall (Gwl) with altered specificity in vitro, another protein kinase recently implicated in mitotic entry in Drosophila and Xenopus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
117
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(139 citation statements)
references
References 42 publications
13
117
0
Order By: Relevance
“…It has been shown that GWL accelerates mitotic progression in various cell types, including those of Xenopus, Drosophila, and human [11,[13][14][15][16][17]. Therefore, we researched whether overexpression of GWL would induce meiotic resumption in porcine oocytes.…”
Section: Overexpression Of Gwl During Meiotic Maturationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that GWL accelerates mitotic progression in various cell types, including those of Xenopus, Drosophila, and human [11,[13][14][15][16][17]. Therefore, we researched whether overexpression of GWL would induce meiotic resumption in porcine oocytes.…”
Section: Overexpression Of Gwl During Meiotic Maturationmentioning
confidence: 99%
“…Depletion of GWL from interphase prevents entry into M phase, whereas overexpression of GWL accelerates entry into M phase in several species, including Drosophila, Xenopus, and human [11][12][13][14][15][16][17]. Moreover, depletion of GWL from mitotic egg extracts leads to exit from M phase by activation of PP2A [12,18].…”
Section: Introductionmentioning
confidence: 99%
“…Thus PP2A is a good candidate for the Greatwall antagonist. In Drosophila, Greatwall (gwl) antagonizes Polo kinase and recessive gwl mutants delay mitotic commitment, suggesting that Greatwall involvement in feedback control is likely to be conserved across species [29,30]. Thus there is much yet to learn about feedback loop amplification and it will be important to test the insights gained in one system in others to differentiate between universal elements of cell cycle control and specific adaptations to the demands of particular lifestyles.…”
mentioning
confidence: 99%
“…26,28,36,39,40,[45][46][47] Starfish and Drosophila have only one MASTL/Greatwall substrate, and the pig ENSA gene has a premature stop codon, such that porcine cells would not express functional ENSA protein. 40 Xenopus oocytes may rely solely or primarily on ARPP19 to regulate exit from prophase I arrest, 36,37 while the data here clearly indicate that ENSA is important for exit from prophase I arrest in mouse oocytes.…”
Section: Discussionmentioning
confidence: 99%